Faktor yang Berhubungan dengan Tindakan Vaksinasi Covid-19 di Kecamatan Tarowang Kabupaten Jeneponto - Rizky Nur Indah; Ella Andayanie; Ulfa Sulaeman (Window of Public Health Journal, 2025)
The coronavirus is a positive, single-stranded RNA virus, encapsulated and non-segmented. The coronavirus belongs to the order Nidovirales, specifically the family Coronaviridae. The structure of the coronavirus forms a cube-like shape with the S protein located on its surface. This type of research uses a quantitative analytical approach with a cross-sectional design. The population in this study is the coronavirus in the Tarowang District, Jeneponto Regency. Data analysis employs multiple logistic statistical tests to examine the relationship between independent variables and dependent variables. The perceived susceptibility variable has no relationship with the action of COVID-19 vaccination in Tarowang District, Jeneponto Regency. The perceived severity variable has no relationship with the action of COVID-19 vaccination in Tarowang District, Jeneponto Regency. The self-efficacy variable has a relationship with the action of COVID-19 vaccination in Tarowang District, Jeneponto Regency. The cue-to-action variable has no relationship with the action of COVID-19 vaccination in Tarowang District, Jeneponto Regency.